2004
DOI: 10.1021/ja047980y
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Alkyl to Aryl Migration and Cyclization:  An Efficient Synthesis of Fused Polycycles via Multiple C−H Activation

Abstract: A novel palladium migration methodology for the synthesis of complex fused polycycles has been developed. This process involves 1,4-palladium alkyl to aryl migrations via through-space C-H activation, followed by intramolecular arylation or an intermolecular Heck reaction providing a very efficient way to synthesize fused ring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(89 citation statements)
references
References 17 publications
2
86
0
1
Order By: Relevance
“…The chiral furan derivatives and polycycles used in this study were synthesized as reported previously, and their structures were confirmed by 1 H-NMR and 13 C-NMR spectroscopy [20,21]. Hydroxypropyl-b-CD (HP-b-CD) and hydroxypropyl-g-CD (HP-g-CD) were acquired from Aldrich Chemical (Milwaukee, WI, USA), with degrees of substititution of 0.8 and 0.6, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chiral furan derivatives and polycycles used in this study were synthesized as reported previously, and their structures were confirmed by 1 H-NMR and 13 C-NMR spectroscopy [20,21]. Hydroxypropyl-b-CD (HP-b-CD) and hydroxypropyl-g-CD (HP-g-CD) were acquired from Aldrich Chemical (Milwaukee, WI, USA), with degrees of substititution of 0.8 and 0.6, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Yao and co-workers [20,21] have synthesized a series of new highly hydrophobic, chiral furans, and fused polycycles. Often different enantiomers of a compound have different biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…8, 9 This type of migration also occurs from aryl palladium to imidoyl palladium, 10 from vinyl palladium to aryl palladium, 11 and from alkyl palladium to aryl palladium. 12 The dppm ligand also facilitates the activation of alkyl C-H bonds to form cyclopropanes (eq 6). 13 …”
Section: C-h Activation and Palladium Migration In Heck Andmentioning
confidence: 99%
“…While this reaction works extremely well for most substituted acetophenones, benzophenone and 4-methoxyacetophenone gave low yields (12% and 8%, respectively) under the same conditions. 15 An environmentally benign variation has been developed using homogeneous catalysts formed in situ from the iron salt [Fe 3 (CO) 12 ], 2,6-bis(2pyridyl)pyridine (terpy), and either dppm or PPh 3 , but in this case the catalyst incorporating dppm was less efficient than that incorporating PPh 3 (eq 10). 16 Reductive Carbonylation.…”
Section: C-h Activation and Palladium Migration In Heck Andmentioning
confidence: 99%
“…[51] Norbornene was again found responsible for the unusual coupling of 3-iodo-1-p-tosylindole 18. [52] Oxidative addition and syn-addition of norbornene to Pd II , is then followed by a 1,4-Pd shift to the 2-position of the indole. Final intramolecular cyclisation to the tosyl group affords the fused-ring system in 19 (Scheme 10).…”
Section: Heck Reactionsmentioning
confidence: 99%